Answer:
X=12
X=4
Explanation:
Step-1 : Multiply the coefficient of the first term by the constant 1 • 48 = 48
Step-2 : Find two factors of 48 whose sum equals the coefficient of the middle term, which is -16 .
-48 + -1 = -49
-24 + -2 = -26
-16 + -3 = -19
-12 + -4 = -16 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -12 and -4
x2 - 12x - 4x - 48
Step-4 : Add up the first 2 terms, pulling out like factors :
x • (x-12)
Add up the last 2 terms, pulling out common factors :
4 • (x-12)
Step-5 : Add up the four terms of step 4 :
(x-4) • (x-12)
Which is the desired factorization